Serum uric acid level is associated with renal arteriolar hyalinosis and predicts post-donation renal function in living kidney donors - Yuzuki Kano; Katsuyuki Tanabe; Masashi Kitagawa; Hitoshi Sugiyama; Tomoaki Yamanoi; Kasumi Yoshinaga; Kensuke Bekku; Shingo Nishimura; Motoo Araki; Jun Wada (PLoS ONE, 2025)
Major guidelines for living-donor kidney transplantation underscore the need for pre-donation evaluation of renal function, hypertension, obesity, diabetes mellitus, and albuminuria to minimize the risk of donation from marginal donors. However, validity is yet to be established. We retrospectively investigated the relationship between clinical characteristics and histological indices in baseline renal biopsies (0-h biopsies) and whether these parameters could predict renal function in living kidney donors one year post-donation. Seventy-six living kidney donors were recruited for this study. In histological analyses, glomerulosclerosis, arteriosclerosis, arteriolosclerosis, arteriolar hyalinosis, and interstitial fibrosis and tubular atrophy scores/indices were evaluated. Post-donation serum creatinine levels in kidney donors with arteriolar hyalinosis were significantly higher than those in individuals without arteriolar hyalinosis. There was a significant correlation between baseline serum uric acid levels and the arteriolar hyalinosis index, with baseline uric acid level identified as an independent factor for hyalinosis in multiple regression analysis. Additionally, the serum uric acid level was a significant prognostic factor for post-donation serum creatinine after adjustment for baseline clinical parameters. These data demonstrate that pre-donation serum uric acid levels are associated with arteriolar hyalinosis in the kidney and could predict a decline in renal function during the first year after donation in living kidney donors.